PRAGMA-SEMIOTIC ANALYSIS OF KOLANUT RITUAL IN TRADITIONAL MARRIAGE CEREMONIES IN NIKE (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
The people of Nike perform different rituals to enact a marriage contract but the most crucial of them is the Ita oji nwanyi (the consumption of bridal kola). Despite its centrality to traditional marriage contract, there is scarcity of linguistic scholarship on the language, acts and symbols that characterize it in Nike. This study is, therefore, a pragma-semiotic inquiry into the major pragmatic acts that characterize the textual and visual communications in Ita oji nwanyi, its semiotic dynamics, and to relate them to the broader context of traditional marriages in Nike. The data were sourced from twelve different traditional marriage ceremonies held within the villages of Nike through observations and interviews spanning a period of fifteen months (November 2021 through February 2023). The study is guided by some of the analytic categories provided in Mey’s (2001) theory of Pragmatic Acts and Kress and Leeuwen’s (2001) socio- semiotic multi-modal analytic approach. While the textual component of the data relating to linguistic features was analysed using Mey’s theory of pragmatic acts, the visual component relating to the non-linguistic features was addressed following Kress and Leeuwen’s socio-semiotic approach to multimodal analysis.  The result revealed that the rituals of Ita oji nwanyi in Nike were enacted through six specific practs which include the practs of welcoming, intention expression, questioning, kola presentation, vowing and blessing while dynamics like day/time, location, and symbolic object constitute the semiotic elements. The practs were realized through the interaction of items in the activity part such as psychological and physical acts with context elements like MPH, SCK, INF, and REL. All of these practs constitute a major situational prototype in the data which is the pragmeme of betrothing.
Keywords: Nike,Marriage,Kolanut,Pragmatics,Semiotics